2007
DOI: 10.1021/bi700467k
|View full text |Cite
|
Sign up to set email alerts
|

PKCε Increases Phosphorylation of the Cardiac Myosin Binding Protein C at Serine 302 both in Vitro and in Vivo

Abstract: Cardiac myosin binding protein C (cMyBPC) phosphorylation is essential for normal cardiac function. Although PKC was reported to phosphorylate cMyBPC in vitro, the relevant PKC isoforms and functions of PKC-mediated cMyBPC phosphorylation are unknown. We recently reported that a transgenic mouse model with cardiac-specific overexpression of PKCepsilon (PKCepsilon TG) displayed enhanced sarcomeric protein phosphorylation and dilated cardiomyopathy. In the present study, we have investigated cMyBPC phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 54 publications
3
29
0
Order By: Relevance
“…31 Apart from PKA, cMyBP-C can be phosphorylated by Ca 2ϩ -calmodulin-dependent kinase (CaMK) 32,33 and PKC. 34,35 Transgenic mice hearts in which the phosphorylation sites of cMyBP-C were changed to nonphosphorylatable alanines displayed reduced contractility and altered sarcomeric structure, indicating that phosphorylation of cMyBP-C is essential for normal cardiac function. 36 Reduced cMyBP-C phosphorylation has been observed in animal models of cardiac hypertrophy and failure 36,37 and in humans with end-stage idiopathic and ischemic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…31 Apart from PKA, cMyBP-C can be phosphorylated by Ca 2ϩ -calmodulin-dependent kinase (CaMK) 32,33 and PKC. 34,35 Transgenic mice hearts in which the phosphorylation sites of cMyBP-C were changed to nonphosphorylatable alanines displayed reduced contractility and altered sarcomeric structure, indicating that phosphorylation of cMyBP-C is essential for normal cardiac function. 36 Reduced cMyBP-C phosphorylation has been observed in animal models of cardiac hypertrophy and failure 36,37 and in humans with end-stage idiopathic and ischemic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also showed that PKCβII phosphorylated the PKA sites Ser23/24 in wild-type myofibrils and demonstrated that such cross-phosphorylation resulted in a rightward shift of the pCa-tension curve (Table 1) (Wang et al 2006). In a more recent study by Lu et al (2010), pseudophosphorylation of Thr143 with glutamic acid (T143E) and of Ser23/24 with aspartic acid (S23D/S24D/T143E) caused no alterations in Ca 2+ -sensitivity upon exchange with cTn(T143E) compared (Xiao et al 2007). -TG mice with alanine substitution of phosphorylation sites displayed depressed cardiac contractility and altered sarcomeric structure (Sakthivel et al 2005).…”
Section: Thin Filament Regulationmentioning
confidence: 92%
“…Mohamed et al (1998) demonstrated that site Ser1169 in chicken is phosphorylated by PKC to 2.0 mol phosphate/mol. Xiao et al (2007) reported that Ser302 on mouse cMyBP-C is a PKCε phosphorylation site both in vivo and in vitro. A specific role for PKC-mediated phosphorylation of cMyBP-C on the contractility and during heart failure has yet to be determined.…”
Section: Cardiac Mybp-c Contains Several Pkc Phosphorylation Sitesmentioning
confidence: 99%
“…For example, mAb specifically recognizing phosphorylated and unphosphorylated TnI at Ser23/24 (human sequence) have been commercially developed, and widely used in studies involving measurement of TnI phosphorylation. It is noteworthy that mAb recognizing phosphorylation within specific sequence motifs have been rapidly developed and increasingly used in myofilament protein studies [94,95]. When a phosphorylation-site-specific antibody is not available, MS can be employed.…”
Section: Phosphorylationmentioning
confidence: 99%